Pengaruh Ukuran Perusahaan, Penjualan, Debt To Equity Ratio terhadap Petumbuhan Laba pada Sub Sektor Industri Food and Beverage yang terdaftar di BEI Periode 2015-2020 - Diki Martin Pangihutan Sinurat (Universitas Batanghari Jambi, 2021)
The purpose of this study is to determine and analyze the influence of Independent Commissioners, Audit Committees, Institusional Ownership, and Managerial Ownership (Good Corporate Governance) on Tax Avoidance in Companies and Banks in Indonesia. The method used in this research in quantitative. The data are secondary data obtained from the anancial statements of Banking Companies listed on the Indonesian Stock Exchange for the 2015 – 2020 period. The population and the sampel used are Bank Companies that are under the auspices of BUMN (State Owned) with a total of four companies. The analytial method used is multiple linier analysis. Based on the results of the tests carried out in this study, can be seen from the F test and t test. Can be seen in the F test with result Fcount with FTable with significant level α = 0,05 can be known Fcount as big as 10,593 by comparing Ftable α = 0,05 with degress of freedom (df) n-k-1 or 24-4-1 = 19 Ftable value of 2,90 Fcount bigger than Ftable (10,593 > 2,90). The result on the t test partially Independent board of commisioners does not have a signifcant effect on tax avoidance with a significant 1,325 , Audit committees not have a significant effect on tax avoidance with a significant 0,522, Institusional ownership has a significant effect on tax avoidance with a significant 3,724, and Managerial Ownership not have a significant effect on tax avoidance with a significant 0,552. The results of this study can be concluded that simultaneously hassignificant effect on the independent variabel that is Independent Commissioner (X1) , Audit Committees (X2), Institusional Ownership (X3), and Managerial Ownership to the dependent variabel that is Tax Avoidance (Y).